Magnetically Separable Fe3O4@poly(m‐phenylenediamine)@Cu2O Nanocatalyst for the Facile Synthesis of 5‐phenyl‐[1, 2, 3]triazolo[1, 5‐c]quinazolines. Issue 5 (28th January 2022) - Rawat, Manish; Taniike, Toshiaki; Rawat, Diwan S.
Abstract: Herein we report a facile approach for the preparation of a magnetically separable Fe3 O4 @poly( m ‐phenylenediamine)@Cu2 O nanocatalyst and its catalytic efficiency in the synthesis of 5‐phenyl‐[1, 2, 3]triazolo[1, 5‐c]quinazolines from ( E )‐1‐bromo‐2‐(2‐nitrovinyl)benzenes, aldehydes, and sodium azide under mild reaction condition is described. The morphology, chemical composition, interior structure and magnetic properties of the Fe3 O4 @PmPDs@Cu2 O nanocomposites were studied using powder X‐ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, energy dispersive X‐ray spectroscopy, X‐ray photoelectron microscopy, vibrating sample magnetometer and nitrogen adsorption‐desorption technique. The as‐prepared Fe3 O4 @PmPDs@Cu2 O nanocatalyst was simply recovered using external magnet and reused up to successive six runs with no obvious loss in its catalytic efficiency and structural integrity (confirmed by powder X‐ray diffraction and transmission electron microscopy of recycled nanocatalyst) along with low leaching of copper (2.32 ppm) and iron (0.008 ppm) ions. The present protocol has a broad substrate scope with high yield in shorter reaction time and it does not require any additive or base. Overall, it has better green chemistry metrices like low E‐factor (0.93), process mass intensity (1.93), high reaction mass efficiency (51.9 %) and carbon efficiency (95 %). Abstract : Magnetic nanocatalysts : Facile synthesis of magnetically recyclable Fe3 O4 @PmPDS@Cu2 O nanocomposites and its catalytical ability was explored for the synthesis of 5‐phenyl‐[1, 2, 3]triazolo[1, 5‐c]quinazolines from ( E )‐1‐bromo‐2‐(2‐nitrovinyl)benzenes, aldehydes, and sodium azide under mild reaction conditions. Nanocatalyst was recycled and reused up to six runs with low leaching of copper and iron ions.